PELATIHAN DESAIN GRAFIS DENGAN METODE BERBASIS PROYEK BAGI ANAK BERKEBUTUHAN KHUSUS DI SLBN PURBALINGGA (Jurnal AbdiMas Nusa Mandiri, 2025)
The Graphic Design Training for Children with Special Needs at SLBN Purbalingga is a community service initiative through the Amikom Mitra Masyarakat (AMM) program aimed at improving inclusive education quality. It focuses on developing graphic design skills for students with special needs, helping them become more independent and prepared for future challenges. The program began with an in-depth situational analysis to identify students and the school’s potential and challenges. Structured solutions were implemented through intensive training sessions covering graphic design basics, software usage, and creative, applicable projects. As a result, students showed significant improvement, creating visual projects like posters and becoming more active and motivated. The assessment through the visual design rubric, which includes aspects of composition, color usage, typography, and other technical skills, shows a higher average score at the end of the learning period compared to the initial scores. Teachers reported increased student participation and enthusiasm. Evaluations with students, teachers, and the Amikom Purwokerto team confirmed the program’s effectiveness, highlighted areas for improvement, and provided feedback for future initiatives. This comprehensive, project-based approach not only enhances students technical skills but also strengthens the foundation of competitive, effective inclusive education in Purbalingga. The initiative aims to deliver lasting positive impacts, equipping students to face future challenges while supporting a sustainable, inclusive educational environment.
Keywords: children with special needs; graphic design training; inclusive education; slb